ANALISIS YURIDIS PENGATURAN TENTANG PERKAWINAN TANPA IZIN ISTERI PERTAMA MENURUT PASAL 279 KUHP BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR: 75 K/PID/ 2016 & 168 K/MIL/2016 - Dandy Gilang Mandala Putra Azwan; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Unregistered marriage (Siri Marriage) is essentially part of the religion of Islam and the practice is allowed in the Islamic religion. The culture of Siri marriage is adopted from the Arabs. Not only in the East, this practice is also extended to Indonesia. The thing is because the majority of Indonesian people are Muslims. The practice of unregistered marriage has been around for a long time and is still present sometimes. Marriage (registered one) which is a symbol of purity and commitment in a household can be an impact of this practice of unregistered marriage. Because marriage sometimes can be littered with infidelity, often unregistered marriage becomes a way out for polygamists. This led to polygamy perpetrators being ensnared by the existence of criminal lawregarding criminal acts regulated in Article 279 of the Criminal Code (hereinafter referred to as the Criminal Code) with the threat of imprisonment of 5 years. In other words, a person is punishable by a five-year prison sentence for a second marriage without permission from his first wife or husband who is still legally bound to the marriage and is still alive. However, the application of this Article is still considered lacking in law enforcement due to the application of juriprudence in Indonesia is not an obligation for judges that give them the liberty to interpret the Article according to their beliefs. This type of research can be classified into the type of Normative legal research which reveals legislation relating to legal theories that are the object of research. The approach taken is qualitative analysis by looking at data both in books, journals, and other scientific works related to this research. The data sources used for this exercise are primary and secondary legal materials.Keywords: Siri Marriage, Criminal Acts, Marriage, Article 279 of the Criminal Code.